A MEASURE AGAINST POLLUTION WASTE SORTING IN NORTH CYPRUS: OPINIONS OF MUNICIPAL AUTHORITIES ON THIS ISSUE - Serkan Ilseven; Almukhtar Aljatlawe (International Journal of Innovations in Engineering Research and Technology, 2023)
North Cyprus is a territory on the third largest ranking mediterranean island, it occupies about 3,241 square kilometers with a total population of about 326,000 people. This study investigates the attitudes and behaviors of municipal waste workers in regards to waste separation and sorting practices in North Cyprus. The study carried out a survey among the municipal SWM workers to evaluate their knowledge in waste separation, their perceptions of the municipality’s processes of SWM, their perceptions on the importance of waste separation in North Cyprus, as well as get their feedback on ways and methods to improve waste separation practices in North Cyprus. Findings on the survey study have indicated poor and inadequate practices of waste separation in North Cyprus that need development and restructuring. The study also found out that the SWM practices on North Cyprus are inadequate as perceived by the municipal workers, and have suggested improvement of the facilities and amenities of SWM in the municipalities. Opinions of respondents also suggest more needs to be done in raising awareness in both SWM municipality workers, and the general public to ensure waste separation practices are adopted in efforts of SWM which they all agreed is important for the country.